Reversible Ubiquitylation in Plant Biology - Hongyong Fu (Frontiers Research Topics, 2015)
Reversible ubiquitylation plays an important regulatory role in almost all aspects of cellular and organismal processes in plants. Its pervasive regulatory role in plant biology is primarily due to the involvement of a large set of ubiquitin system constituents (encoded by approximately 6% Arabidopsis genome), the huge number of important cellular proteins targeted as substrates, and various drastic effects on the modified proteins. The major components of the ubiquitin system include a large set of enzymes and proteins involved in ubiquitin conjugation (E1s, E2s, and E3s) and deconjugation (deubiquitinases of different classes) and post ubiquitin conjugation components such as ubiquitin receptors, endocytic machineries, and 26S proteasome. The established substrates include transcriptional activators and repressors, signaling components, key metabolic enzymes, and critical mechanistic components of major cellular processes and regulatory mechanisms. Post-translational modification of proteins by reversible ubiquitylation could drastically affects the modified proteins by proteolytic processing and turnover, altering catalytic activity, subcellular targeting, and protein-protein interaction. Continued efforts are being carried out to identify novel substrates critical for various cellular and organismal processes, to determine effects of reversible ubiquitylation on the modified substrates, to determine signaling determinants triggering reversible ubiquitylation of specific substrates, to illustrate individual components of the ubiquitin system for their in vivo functions and involved mechanistic roles, and to determine mechanistic roles of modification acting on critical components of major cellular processes and regulatory mechanisms. The aim of this special topic is to serve as a platform to report most recent advances on those above listed current research endeavors. We welcome article types including original research, review, mini review, method, and perspective/opinion/hypothesis.